PENGUAPAN AIR DAN PENYUSUTAN IRISAN UBI KAYU SELAMA PROSES PENGERINGAN MENGGUNAKAN MESIN CABINET DRYER - Mima Purwanti; Jamaluddin P Jamaluddin P; Kadirman Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research was aims to determine the mechanism of water vaporization and shrinkage in cassava chips during drying process using a cabinet dryer machine. Cassava chips driedat temperature 50, 60, and 700C with the time 240, 300, and 360 minutes. The parameter observed werewater content, water vaporization and shrinkage. The data were analyzed of descriptive. The results of the research showed that during drying process occurred of changes water content, water vaporization and shrinkage. More high  the temperature and to the length of time drying cause decrease the water content with increase the rate water vaporization and shrinkage.